2020
DOI: 10.33003/fjs-2020-0402-195
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Poultry Manure and Weed Control Methods on Growth and Yield of Sesame Varieties

Abstract: Field trials were conducted in 2017 and 2018 wet seasons at Federal University Dutse Teaching and Research Farm (Latitude 11 46, 39”N and Longitude 9 20, 30”E) in the Sudan Savanna of Nigeria. To evaluate performance of sesame varieties as affected by poultry manure and weed control methods. The treatments consisted of five weed control treatments (pre-emergence application of ButachlorEC50%,  hoe weeding at 3WAS +pre-emergence butachlor EC50%, pre-emergence butachlor EC50%+hoe weeding at 3 and 6WAS, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The better economic yield may have resulted from sufficient nutrient availability from both organic and inorganic sources at the right moment, which enabled for the optimum dry matter partitioning from the source to sink during the plant's reproductive stage and considerably increased the soybean seed production. Danmaigoro (2020) reported that application of poultry manure promoted vegetative growth in sesame consequently resulting in the increase in number of capsules produced, better seed formation and filling which led to the higher seed yield. Falodun et al (2015) reported that the combination of organic and inorganic fertilizers adequately supply nutrient element at the right time from organic and inorganic sources which helped optimum dry matter partitioning from the source to sink during reproductive stage of plant consequently increase the seed yield of soybean.…”
Section: Yield and Yield Attributesmentioning
confidence: 99%
See 1 more Smart Citation
“…The better economic yield may have resulted from sufficient nutrient availability from both organic and inorganic sources at the right moment, which enabled for the optimum dry matter partitioning from the source to sink during the plant's reproductive stage and considerably increased the soybean seed production. Danmaigoro (2020) reported that application of poultry manure promoted vegetative growth in sesame consequently resulting in the increase in number of capsules produced, better seed formation and filling which led to the higher seed yield. Falodun et al (2015) reported that the combination of organic and inorganic fertilizers adequately supply nutrient element at the right time from organic and inorganic sources which helped optimum dry matter partitioning from the source to sink during reproductive stage of plant consequently increase the seed yield of soybean.…”
Section: Yield and Yield Attributesmentioning
confidence: 99%
“…Poor soil fertility is a generally known issue that serves as a key barrier to optimizing agricultural productivity (Hilhorst et al, 2000). Soils of the savannah regions are known to contain low nitrogen that are inadequate to sustain good growth and development of some crop plants (Danmaigoro, 2020). Agricultural lands in Kano state, Northern Nigeria like their counterparts in Sub-Saharan Africa are inherently low in fertility and are subjected to numerous natural challenges imposed by the harsh climatic conditions that ensue in this agro ecological zone (Rabiu, 2015).…”
Section: Introductionmentioning
confidence: 99%